The clinical and radiological characterizations of allergic phenotype in chronic rhinosinusitis with nasal polyps - Vengathajalam, Selvamalar (2020)
Objectives: Allergic phenotype has recently been described as a subset of chronic rhinosinusitis with polyps (CRSwNP) and without polyps (CRSsNP). Our aim is to explain the clinical characterizations with symptoms and endoscopic Lund Kennedy scoring as well as radiological characterizations with Lund Mackay scoring of patients with the allergic phenotype of CRSwNP. The importance of this study is to determine the association of allergy and CCAD to CRSwNP that will aid in further understanding of the pathophysiology of the disease and managing the patients accordingly. Methods: A cross-sectional studyon patients diagnosed with CRSwNP who had both allergology and radiological assessments. Theoverall nasal symptoms score including 3 rhinologic problems, with relevance to allergy (need to blow nose, sneezing, and runny nose), Lund Kennedy (LK) endoscopic scoring, Lund Mackay (LM) scoring of computed tomography (CT) scan of the paranasal sinuses (PNS), central compartment atopic disease (CCAD) features, skin prick test (SPT) and level of specific IgE were assessed. Results: There was no difference in overall symptoms score but there was a higher allergy symptoms burden in atopy and CCAD groups. There was significant difference in the endoscopic and CT PNS scores between atopy and non-atopy as well as CCAD and non CCAD. CCAD has a significantly association with atopy and has a higher endoscopic and CT PNS scores. Conclusions: Atopy and its radiological phenotype, the CCAD must be properly assessed in patients with CRSwNP as they may determine the clinical and radiological severity. Patients with atopy and CCAD have more polypoidal involvement of the middle turbinates, additional symptoms burden and higher endoscopic and CT PNS scoring proving that there is an association between allergy and CRSwNP.